Financing Micro Firms in Europe: An Empirical Analysis - Christian Masiak; Joern H. Block; Alexandra Moritz; Frank Lang; Helmut Kraemer-Eis (European Investment Fund (EIF), 2017)
The vast majority of firms in Europe are micro firms. Still, we know little about their financing patterns. Our paper aims to close this gap. Based on a large European firm-level data set, we find that micro firms differ in their financing patterns from small and medium-sized companies. Our empirical results show that micro firms are more likely to use internal financing instruments, whereas they are less likely to use state subsidies, trade credit or asset-based financing instruments. Furthermore, micro firms differ from medium-sized firms by using more short-term debt (credit card overdrafts, credit lines and bank overdrafts). The implications of these findings for micro firms and policy makers are discussed.
Keywords: C30; G20; G30; 330; Micro firms; SMEs; enterprise financing in Europe; financing patterns